THE LACK OF CORRELATION IN TYPE 2 DIABETES MELLITUS BETWEEN NON-CPG METHYLATION AND DIABETES RISK FACTORS, LIPID PROFILE, KIDNEY FUNCTION TEST, HBA1C, AND RANDOM BLOOD SUGAR - Smail, Harem O. (Science Journal of University of Zakho, 2024)
Background: Chronic hyperglycemia and insulin resistance are two hallmarks of type 2 diabetes mellitus (T2DM), a complicated metabolic disease. The purpose of the current investigation was to identify Non-CPG methylation in the ABCC8 and CAPN10 promoter regions. Method: Fifty people were divided into two groups: thirty-five were diagnosed with type 2 diabetes mellitus, and fifteen were control group. Utilizing direct bisulfite sequencing to identify Non-CPG methylation in the promoter region and determine the extent of DNA methylation. To ascertain whether a result was statistically significant at the level of significance 0.05, the T-independent test, Spearman's correlation, and Chi square tests were performed. Results: Hypermethylation of DNA has been found in the diabetes promoter region of the CAPN10 and ABCC8 genes compared to the healthy group. Furthermore, Non-CPG methylation in both genes and the statistically significant CAPN10 gene has not been linked to risk factors or biochemical indicators. Conclusion: This study concluded that the biochemical biomarkers and risk factors did not influence Non-CPG methylation of selected genes in type 2 diabetes mellitus